2001
DOI: 10.1186/1471-2296-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding childhood asthma in focus groups: perspectives from mothers of different ethnic backgrounds

Abstract: Background: Diagnosing childhood asthma is dependent upon parental symptom reporting but there are problems in the use of words and terms. The purpose of this study was to describe and compare understandings of childhood 'asthma' by mothers from three different ethnic backgrounds who have no personal experience of diagnosing asthma. A better understanding of parents' perceptions of an illness by clinicians should improve communication and management of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
1
25
0
3
Order By: Relevance
“…The present general population-based results confirm and supplement findings from hospital-based populations, which showed limited understanding of the term wheeze by parents [8,9,21]. It has been suggested that a video questionnaire might avoid the problem of misunderstandings inherent to written questionnaires.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
See 1 more Smart Citation
“…The present general population-based results confirm and supplement findings from hospital-based populations, which showed limited understanding of the term wheeze by parents [8,9,21]. It has been suggested that a video questionnaire might avoid the problem of misunderstandings inherent to written questionnaires.…”
Section: Comparison With Other Studiessupporting
confidence: 82%
“…Recent studies of hospital-based samples of children have challenged the validity of parent-reported wheeze, by showing that conceptual understanding of wheeze by parents differed from the definitions used by epidemiologists [8] and that parental understanding differed between ethnic groups [9]. To avoid such misunderstandings, it has been suggested that the term wheeze should be explicitly defined in questionnaire surveys [8].…”
mentioning
confidence: 99%
“…Anne babaların solunum yolu sesleri için kullandıkları tanımların eğitim düzeyi, sosyoekonomik düzey, etnik köken, ailede allerjik hastalık öyküsü olup olmaması, cinsiyete göre farklılık gösterdiği bilinmektedir (4,5,7,13). Michel ve ark.…”
Section: Gereç Ve Yöntemlerunclassified
“…Vizing İngilizce kökenli bir kelimedir ve İngilizcenin anadil olduğu ülkelerde aileler sağlık kuruluşlarına çocuklarında vizing olduğunu söyleyerek başvururlar. Ancak anadili İngilizce olmayan ülkelerde aileler vizing semptomunu tarif etmek için farklı terminolojiler kullanarak sağlık kuruluşuna başvurabilirler (4)(5)(6).…”
Section: Introductionunclassified
See 1 more Smart Citation